Menyikapi Musibah Alam: Suatu Upaya Meluruskan Kegelisahan Teologi - Rahmani Timorita Yulianti (Universitas Islam Indonesia, 2005)
The disasters that happen Indonesia. One of them is tsunami at Aceh, North Sumatra and Nias. When disasters happen, people confuse how to solve them. In this case, people hope to know the factois that cause eartyhquake by ultimate questions. This discourse of course includes theology or philosophical viewpoint. In this connection the question is what God's reason behind of earthquake or disasters that imply many victims. Meanwhile, Aceh denotes religious field, instead this province implements Islamic Syari'ah. According to the writer of this article that disaster or earthquake happens because of human errors.